DOI: 10.11606/d.61.2010.tde-29072010-104318
|View full text |Cite
|
Sign up to set email alerts
|

Drenagem linfática manual no pós-operatório de enxerto ósseo alveolar: uma nova abordagem para a redução do edema facial

Abstract: DedicatóriaDedico este trabalho aos meus queridos pais, Otavio e Roseli, que são meus grandes amores, meus maiores tesouros, exemplos de vida e de amor incondicional. A eles coloco toda minha admiração.Espero um dia poder retribuir um pouquinho de todo amor, carinho, atenção e cuidados que sempre dedicam a mim. E aos meus queridos irmãos, Joaquim e Eduardo, pela amizade, companheirismo e afeto.Em especial aos meus avôs, Waldemar e Jeannette, Alice e Joaquim por todo carinho. Suas experiências, seus conselhos e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
6

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
2
0
6
Order By: Relevance
“…19 However, some authors recommend that the temporary reduction in mandibular movements without therapeutic rehabilitation favors their full rehabilitation, which can occur anywhere from six months to two years. 1,15,16,17,18,19,20,21,22,23 Although mandibular movements increased over 2 months post-surgery, both protocols had similar mean values, namely 33 mm for opening, and 5 to 6 mm for laterality (Table 5). These values are low compared with those recommended in the Genaro et al 9 protocol, namely 6 to 12 mm for laterality, and 40 to 55 mm for mouth opening.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…19 However, some authors recommend that the temporary reduction in mandibular movements without therapeutic rehabilitation favors their full rehabilitation, which can occur anywhere from six months to two years. 1,15,16,17,18,19,20,21,22,23 Although mandibular movements increased over 2 months post-surgery, both protocols had similar mean values, namely 33 mm for opening, and 5 to 6 mm for laterality (Table 5). These values are low compared with those recommended in the Genaro et al 9 protocol, namely 6 to 12 mm for laterality, and 40 to 55 mm for mouth opening.…”
Section: Discussionmentioning
confidence: 95%
“…Chung How Kau et al also observed that the edema is greater in the first 3 days after surgery, but improves significantly over time, without related therapeutic intervention. 16 Ferreira 17 recommends that the speech therapist should instruct and supervise the patient in performing manual lymphatic drainage (MLD), since there is the risk that the treatment will not be performed correctly if the patient lacks follow-up. The MLD in the protocol of this study did not include the guidelines for the massages to be performed at home by the patients, a factor that could have intensified and modified the results.…”
Section: Discussionmentioning
confidence: 99%
“…A gravidez quando esperada e planejada pela mulher corresponde a um dos momentos mais felizes em sua vida. Após a fecundação e a descoberta da gestação, o vínculo entre a mãe e o feto começa a ser construído e o anseio de um período gestacional tranquilo para um bom desenvolvimento fetal e um bom nascimento se aflora (Ferreira;Lima, 2020).…”
Section: Introductionunclassified
“…O aumento do volume sanguíneo decorrente da produção exacerbada de hormônios como a progesterona e estrogênio e o aumento do útero gravídico pode acarretar no aparecimento do edema gestacional em membros inferiores. O edema pode causar desconforto, dor e limitações funcionais na gestante (Ferreira;Lima 2020).…”
Section: Introductionunclassified
“…O edema trata-se de uma situação anormal, na qual a linfa ultrapassa a capacidade limite do sistema linfático e resulta da insuficiência da drenagem, em que coletores ou gânglios linfáticos estão obstruídos, como na condição inflamatória (FERREIRA, 2010).…”
Section: Introductionunclassified